Quando la materia è politica. Tecniche e linguaggi delle opere di Loredana Longo - Francesca Renda (Papireto)
In Loredana Longo’s works, one often sees an aesthetic contrast between the material used and the way it is treated: explosions, blows, impacts, are the actions reserved for the plastic definition of the final object that appears discomposed, but visually mindful of the energy released. In her works, precious or traditional materials – silk, gold, velvet, clay – are treated in an unconventional way. In the Carpet series (2012-2020), the artist uses an electric soldering iron to engrave iconic phrases on Persian carpets; a similar thing happens in Victory/tapestry (2016-2021), where scenarios of conflict and tragedy appear in negative on velvet, through burns. Raw materials, belonging to the construction sector, are the raw material for some important works such as Floor (2011-2013), in which the artist exploits the aggregating capacity of concrete to create walkable installations, through a mixture of impoverished concrete and common objects (clothes or low-cost porcelain). Particular attention is also paid to ceramics, which takes shape after a long, often performative process. In Gold Heel (2018), the artist interacts with a punching bag that he hits forcefully when the clay is still raw: the sculpture is then fired, leaving visible the artist's imprints. In the Creative Execution series (2019), painted clay vases are arranged in a row and then detonated with gunpowder and electric igniters; the resulting decomposed shape is then blocked by the firing process. We therefore propose an analysis of the techniques used by Loredana Longo in some works that favor malleable raw materials, but worked with a vigor and a method outside traditional schemes. Attention is also paid to social and political references, then moving on to their definition in the framework of the languages of contemporary art.